The effect of gamma irradiation on the germination and growth of Turda Star maize hybrid dry samples - Marcu, Delia; Cosma, Constantin (Acta Agraria Debreceniensis, 2010)
In order to study the effects of gamma rays on germination indices i.e. germination index (GI), total germination (GT) and thegermination energy (GE), of maize hybrid, Turda Star current experiment was conducted. Dry seeds of Turda Star maize hybrid wereirradiated with 2, 5, 15, 30 and 50 Gy, using a 60Co-gamma radiation source.Results showed that gamma irradiation affected all the above mentioned parameters except germination percentage. Totalgermination and germination energy was significantly affected at higher doses of gamma rays. However, increasing doses of gammarays did not have significant effects on seed germination percentage. The other growth parameters showed declining tendency withincreasing doses of gamma irradiation.